Inoculation and nitrogen management to optimize pulse crop yield and protein. Issue 4 (12th July 2018) - Jones, Clain; Olson-Rutz, Kathrin
Abstract : Pulse crops require nitrogen (N) either from the soil or through N gas fixation by rhizobia bacteria in nodules on their roots. This article will discuss the factors affecting nodulation and N fixation, different inoculant types and their effect on yield and protein, starter and rescue N along with the need for other nutrients, and how the economics play out. Earn 1 CEU in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/597 .